Biopsychosocial Functions of Human Walking and Adherence to Behaviourally Demanding Belief Systems: A Narrative Review - O’Mara, Shane (Frontiers in Psychology, 2021)
Human walking is a socially-embedded and shaped biological adaptation: it frees our hands, make our minds mobile, and is deeply health-promoting. Yet, today, physical inactivity is an unsolved, major public health problem. However, globally, tens of millions of people annually undertake ancient, significant, and enduring traditions of physiologically- and psychologically-arduous walks (pilgrimages) of days-to-weeks extent. Pilgrim walking is a significant human activity requiring weighty commitments of time, action, and belief, as well as community support. Paradoxically, human walking is most studied on treadmills, not ‘in the wild’. While mechanistically vital, treadmill studies of walking cannot, in principle, address why humans walk extraordinary distances together to demonstrate their adherence to a behaviourally-demanding belief system. Pilgrim walkers provide a rich ‘living laboratory’ bridging humanistic inquiries, to progressive theoretical and empirical investigations of human walking arising from a behaviourally-demanding belief system. Pilgrims vary demographically, and undertake arduous journeys on precisely-mapped routes of tracked, titrated, doses and durations on terrain of varying difficulty, allowing investigations from molecular to cultural levels of analysis. Using the reciprocal perspectives of ‘inside→out’ (where processes within brain and body initiate, support, and entrain movement), and ‘outside→in’ (where processes in the world beyond brain and body drive activity within brain and body), we examine how pilgrim walking might shape personal, social, and transcendental processes, revealing potential mechanisms supporting the body and brain in motion, to how pilgrim walking might offer policy solutions for physical inactivity.